Integration of General Knowledge and Religion: Strategies for Building Holistic Education in a Multidisciplinary Era - Pitriani, Leni; Hadistia, Mega; Achmad Muharam Basyari (Institut Agama Islam Persis Bandung, 2024)
This article aims to explore strategies for integrating general and religious knowledge within Islamic education as an approach to building a holistic educational system aligned with the demands of the multidisciplinary era. Using a descriptive qualitative method through literature review, this study analyzes integrative practices in Islamic educational institutions, the strategic role of teachers, as well as the challenges and opportunities for strengthening integration. The findings indicate that integration models are implemented through unified curricula, thematic learning, and value-based project assignments that combine scientific and spiritual approaches. Teachers act as key agents who not only deliver subject content but also embody values through interdisciplinary teaching. Despite facing challenges such as dichotomous paradigms, limited teacher competencies, and the scarcity of integrative teaching materials, integration can be strengthened through teacher training, curriculum reform, institutional policies, and collaboration among stakeholders. Through this approach, Islamic education can cultivate insan kamil individuals who are intellectually excellent, spiritually grounded, and globally competitive.